Teacher Candidates’ Responses to Examining Personal Privilege: Nuanced Understandings of the Discourse of Individualism in Critical Multicultural Education - Whiting, Erin Feinauer; Cutri, Ramona Maile (Frontiers in Education, 2019)
Building on scholarship that establishes the Discourse of Individualism as a typical response to critical multicultural education, this study examines emergent discourses from 175 teacher candidates in their explanations of personal privilege. Open codes were applied to end-of-semester written responses from pre-service teachers asking them to explain the unearned privileges in their lives. Data was coded with attention to ideologies and meaning making. Analysis reveals three ways that teacher candidates’ articulate and explain their personal privilege: 1) articulations of personal achievement relying on an ideology of meritocracy (n=12); 2) articulation of inheritance that references an ideology of luck (n=118); and 3) articulations of systemic inequality that begins to evidence more critical ideologies (n=45). These three distinct, yet related, articulations of the Discourse of Individualism extend previous research by documenting the nuanced manner in which students grapple with privilege. Our finding documenting articulations of inheritance represents a discursive space in which students consider the reality of social position and structural inequity in society and open the door for conversations of ways to understand and enact professional obligations to those who are “not lucky.” This finding has practical and theoretical implications for teacher educators and extends previous conceptualizations of the Discourse of Individualism.